Introduction - Virginia Association for Retarded Citizen, Inc.; Central Virginia Educational Television; Virginia Commonwealth University (Columbus, Ohio : Charles E. Merrill Pub. Co., 1976)
Deals with the identification of young children with developmental disabilities, the need for early identification, etc. Also provides information on succeeding programmes.
Keywords: Handicapped children; Child study